Effectiveness of a psychological intervention focused on stress management for women prior to IVF. (14th March 2020) - Heredia, Ana; Padilla, Francisca; Castilla, Jose Antonio; Garcia-Retamero, Rocio
ABSTRACT: Objective : To evaluate the effectiveness of a psychological intervention focused on stress management in women who are candidates for in vitro fertilisation (IVF). Method : Pre–post study with two groups ( n  = 26). The psychological intervention group (IG) received a 90-minute session that included psychoeducation, relaxation training and coping skills. The control group (CG) did not receive any psychological intervention. All participants later underwent IVF. In the initial and final evaluations, state anxiety, emotional imbalance, adaptive resources and quality of life were measured. In the initial evaluation, demographic and clinical variables were also measured. Results : In the IG, the final evaluation reflected: (1) decreased levels of anxiety and emotional imbalance; (2) the perception of enhanced quality of life. Moreover, among the participants who received the psychological intervention and later achieved a successful IVF, the level of anxiety appeared to have decreased more strongly. Conclusions : A brief intervention focused on stress management can benefit the psychological adjustment of women who are candidates for IVF, reducing the anxiety they may experience in this regard. However, our conclusions are based on a small sample, and so should be considered with caution. Nevertheless, these results are promising and highlight the advisability of further research.